2017
DOI: 10.1016/j.ajhg.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Histone Acetylase Modifier BRPF1 Cause an Autosomal-Dominant Form of Intellectual Disability with Associated Ptosis

Abstract: Intellectual disability (ID) is a common neurodevelopmental disorder exhibiting extreme genetic heterogeneity, and more than 500 genes have been implicated in Mendelian forms of ID. We performed exome sequencing in a large family affected by an autosomal-dominant form of mild syndromic ID with ptosis, growth retardation, and hypotonia, and we identified an inherited 2 bp deletion causing a frameshift in BRPF1 (c.1052_1053del) in five affected family members. BRPF1 encodes a protein modifier of two histone acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(93 citation statements)
references
References 29 publications
7
86
0
Order By: Relevance
“…These cases are mainly from North America and Europe, where exome sequencing has been routinely used for clinical diagnosis of rare developmental disorders. As shown in table S1, most of the newly identified 12 individuals share key clinical features with those reported cases (12,33), including general developmental delay and gross/fine motor delay. Many showed intellectual disability and had language delay (table S1).…”
Section: Brpf1 Variants In 12 New Cases Of Syndromic Intellectual Dismentioning
confidence: 70%
See 2 more Smart Citations
“…These cases are mainly from North America and Europe, where exome sequencing has been routinely used for clinical diagnosis of rare developmental disorders. As shown in table S1, most of the newly identified 12 individuals share key clinical features with those reported cases (12,33), including general developmental delay and gross/fine motor delay. Many showed intellectual disability and had language delay (table S1).…”
Section: Brpf1 Variants In 12 New Cases Of Syndromic Intellectual Dismentioning
confidence: 70%
“…2), we then investigated the clinical relevance of these findings. We and others have reported 28 clinical cases of syndromic intellectual disability due to de novo or inherited BRPF1 variants (12,(33)(34)(35). We have now identified 12 previously unreported cases ( Fig.…”
Section: Brpf1 Variants In 12 New Cases Of Syndromic Intellectual Dismentioning
confidence: 85%
See 1 more Smart Citation
“…Individuals with KAT6A mutations also demonstrate other clinical features that overlap with SBBYS and GPS (Table ) (Arboleda et al, ; Millan et al, ; Tham et al, ). BRPF1 , a regulator of both histone lysine acetyltransferases KAT6A and KAT6B , has also very recently been implicated in an intellectual disability syndrome with facial dysmorphisms like blepharophimosis that have similarity with KAT6B spectrum patients, although craniosynostosis has not yet been described (Mattioli et al, ; Yan et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Very interestingly, Yan et al and Mattioli et al identified heterozygous sequence variants in the BRPF1 gene on chromosome 3p25, leading to a phenotype characterized by delayed psychomotor development, intellectual disability, delayed language, and dysmorphic facial features, most notably ptosis/blepharophimosis. Additional features may include poor growth, hypotonia, and seizures (intellectual developmental disorder with dysmorphic facies and ptosis, OMIM #617333).…”
Section: Kat6bmentioning
confidence: 99%